1319. Pharmacokinetics of Ceftolozane/Tazobactam in Patients with Burns. (31st December 2020) - Hall, Ronald G; Pasipanodya, Jotam; Putnam, William C; Griswold, John; Dissanaike, Sharmila; Kallem, Raja Reddy; Edpuganti, Vindhya; Subramaniyan, Indhumathy
Abstract: Background: Antimicrobial dosing in moderate/severe burns patients is complicated due to the potential unpredictable hyperdynamic pathophysiologic states including 1) hypoproteinemia, 2) acute kidney injury and 3) onset of septicemia. Therefore, distribution assumptions about the population pharmacokinetic (PopPK) profiles of either endogenous or xenobiotic pharmacophores in this patient population can lead to biased parameter estimates. In order to prevent potential bias an agnostic nonparametric adaptive grid approach to describe ceftolozane/tazobactam (C/T) PopPK profiles in patients with partial- and full-thickness burns was employed. Methods: A human clinical PK study in burn patients was conducted using the standard approved dose of C/T (2 grams/1 gram). A single intravenous dose was administered over 60 minutes. Whole blood was obtained pre-dose and at 0.5, 1, 1.5, 2, 2.5, 3, 4, 6, 8, 12, 16, and 24 hours following the start of infusion. LC-MS/MS bioanalytical methods were developed, validated and employed to determine C/T concentrations in human plasma. PopPK were modeled using Pmetrics package for R. One-, two- and three-compartment models were examined and compared. The influence of several parameters, including %body surface area burns, creatinine clearance (CrCL), weight, albumin and age were tested. Results: The bioanalytical method for determination of C/T in human plasma met all recommended criteria of the LC-MS/MS. Five males and one female (ages 24 to 66 years), contributed 148 plasma PK samples. The female had 35% partial-thickness burns. The males had full-thickness burns ranging from 27 to 66%. The median CrCL was 104 mL/min (range 73-148 mL/min). Two-compartment model with absorption (Ka) from compartment 1 to 2 and elimination from compartment 2 (Ke), with nonlinear interactions between C/T elimination and CrCL best described the data. Figure A show that bias was minimal. Importantly, both drugs exhibited marked variability for both volume and elimination (Table), since volume was bimodally distributed (Figure B). A) Observation-versus-Prediction; B) Estimated Ke, V and Ka population parameter densities Summary of pharmacokinetic parameters Conclusion: C/T exhibited high variability surpassing that observed with severe infections, suggesting that dose adjustment and/or may be therapeutic drug monitoring may be needed to balance target attainment from dose-related toxicities. Disclosures: Ronald G. Hall, II, PharmD, MSCS, Medical Titan Group (Grant/Research Support)Merck (Research Grant or Support)